Poly(Ionic) Liquid-Enhanced Ion Dynamics in Cellulose-Derived Gel Polymer Electrolytes - Paiva, Tiago G.; Klem, Maykel [UNESP]; Silvestre, Sara L.; Coelho, João; Alves, Neri [UNESP]; Fortunato, Elvira; Cabrita, Eurico J.; Corvo, Marta C. (Wiley, 2025)
Gel polymer electrolytes (GPEs) are regarded as a promising alternative to conventional electrolytes, combining the advantages of solid and liquid electrolytes. Leveraging the abundance and eco-friendliness of cellulose-based materials, GPEs were produced using methyl cellulose and incorporating various doping agents, either an ionic liquid (1-Butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide [Pyr14][TFSI]), its polymeric ionic liquid analogue (Poly(diallyldimethylammonium bis(trifluoromethylsulfonyl)imide) [PDADMA][TFSI]), or an anionically charged backbone polymeric ionic liquid (lithium poly[(4-styrenesulfonyl)(trifluoromethyl(S-trifluoromethylsulfonylimino) sulfonyl) imide] LiP[STFSI]). The ion dynamics and molecular interactions within the GPEs were thoroughly analyzed using Attenuated Total Reflectance Fourier-Transform Infrared Spectroscopy (ATR-FTIR), Heteronuclear Overhauser Enhancement Spectroscopy (HOESY), and Pulsed-Field Gradient Nuclear Magnetic Resonance Diffusion (PFG-NMR). Li+ transference numbers (tLi+) were successfully calculated. Our study found that by combining slow-diffusing polymeric ionic liquids (PILs) with fast-diffusing lithium salt, we were able to achieve transference numbers comparable to those of liquid electrolytes, especially with the anionic PIL, LiP[STFSI]. This research highlights the influence of the polymer′s nature on lithium-ion transport within GPEs. Additionally, micro supercapacitor (MSC) devices assembled with these GPEs exhibited capacitive behavior. These findings suggest that further optimization of GPE composition could significantly improve their performance, thereby positioning them for application in sustainable and efficient energy storage systems.
Keywords: Cellulose; Energy storage; Nuclear magnetic resonance; Poly(Ionic liquids); Supercapacitors